2003
DOI: 10.1093/annonc/mdg164
|View full text |Cite
|
Sign up to set email alerts
|

Predictive testing for BRCA1 and 2 mutations: a male contribution

Abstract: Complex themes associated with genetic testing are confirmed and the spectrum extended. Men appear to understand the importance of participating in this process. Methods of avoiding adverse reactions merit further study along with other aspects of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 25 publications
6
50
1
Order By: Relevance
“…Another qualitative study reports the experiences of men in breast cancer families [12]. Four quantitative studies described the genetic counseling and testing process and outcome of men at risk [13,14], psychological functioning and attitudes during genetic testing [15] and the needs of 59 male carriers [16] (Table 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another qualitative study reports the experiences of men in breast cancer families [12]. Four quantitative studies described the genetic counseling and testing process and outcome of men at risk [13,14], psychological functioning and attitudes during genetic testing [15] and the needs of 59 male carriers [16] (Table 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Several studies denote that males often describe their decision of genetic testing as an obligation to their children, and many described genetic testing as a family duty [7,9,11,15,16]. Even men without daughters and single men wanted a genetic test to show familial solidarity [14]. Some of the studies report a lack of information and exclusion of adult children from decision-making prior to the men's genetic tests [21].…”
Section: Males Decision-making Regarding Genetic Testingmentioning
confidence: 99%
“…15 Studies also report that men from families with hereditary breast/ovarian cancer fear that they will develop breast cancer, are aware that they are at increased risk of prostate and bowel cancer, and have intrusive thoughts about this increased risk. 14,16,17 It has also been reported that men admit to preferring avoidance and denial to cope with their cancer risk, 16,18 avoid discussing their emotions, 16,17 have unresolved grief about past and future losses, and experience guilt about passing on a potentially lethal gene mutation to their future offspring. 17,19,20 Very little is known about men who do not attend FCCs because of difficulties in ascertaining these individuals and/or a lack of interest in participating in research studies.…”
Section: ; Kconfab Investigatorsmentioning
confidence: 99%
“…Parents (BRCA1/2 carriers, non-carriers and their partners), wishing to protect their children from anxiety-provoking information, had deliberately managed the timing of informing their children about undergoing genetic testing, and had found the process difficult whatever strategy they had chosen. Several studies report instances of people not telling their children, either because they were unsure of how or when to do so [21], were unwilling [22], or thought their children too young [9]. Segal et al [23] found that a child's age was the most significant contributing factor in the decision to disclose, with the mean age at disclosure being 24.3 years.…”
Section: Introductionmentioning
confidence: 99%